Design techniques for high performance optical wireless front-ends - Alves, Luís Nero (2012)
Wireless optical networks usually have demanding specifications in terms of bandwidth, dynamic range and sensitivity. The front-end is a critical element for the fulfillment of these demands. This paper discusses several design aspects of front-ends for optical wireless communications, covering techniques for achieving high gains, high input dynamic ranges, improving noise performance, and reducing electromagnetic interference (EMI). The paper further presents some experimental results of many of the techniques here described. The cumulative usage of those techniques significantly increases system performance, in terms of sensitivity, power and bandwidth even with low cost, CMOS technologies.